Efektivitas Pembatasan Penggunaan Gawai dan Keterbatasan Buku Paket Terhadap Proses Pembelajaran Siswa di SMTK Setia Mamuju, Sulawesi Barat - Victor Baitanu; Rut Desinta Simatupang (Vieka Wahana Semesta, 2026)
Abstract: Education plays an important role in helping students develop knowledge, attitudes, and skills through a systematically designed learning process. However, in practice, the implementation of learning often faces limitations in supporting facilities. This research was carried out at SMTK Setia Mamuju to describe the learning process that takes place in conditions of restrictions on the use of gadgets and limited availability of package books. Schools implement a policy of restricting devices to maintain students' learning concentration, while the limitations of package books encourage teachers and students to adjust the learning strategies used. This research uses a descriptive qualitative approach with observation techniques of classroom learning activities, learning assistance, and brief interviews with teachers and students. The learning process is carried out face-to-face by utilizing simple learning resources, such as direct explanations from teachers, group discussions, and the use of concise teaching materials. The results of the study show that the restriction on the use of gadgets does not hinder the learning process if teachers are able to implement strategies that are in accordance with the student's conditions. Although the limitations of package books are still felt, students show increased focus, activeness, and better social interaction. These findings confirm that the educational process can still take place effectively despite the limitations of learning facilities. Abstrak: Pendidikan berperan penting dalam membantu siswa mengembangkan pengetahuan, sikap, dan keterampilan melalui proses pembelajaran yang dirancang secara sistematis. Namun, dalam praktiknya, pelaksanaan pembelajaran sering menghadapi keterbatasan sarana pendukung. Penelitian ini dilaksanakan di SMTK Setia Mamuju untuk menggambarkan proses pembelajaran yang berlangsung dalam kondisi pembatasan penggunaan gawai serta keterbatasan ketersediaan buku paket. Sekolah menerapkan kebijakan pembatasan gawai guna menjaga konsentrasi belajar siswa, sementara keterbatasan buku paket mendorong guru dan siswa untuk menyesuaikan strategi pembelajaran yang digunakan. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan teknik observasi kegiatan pembelajaran di kelas, pendampingan belajar, dan wawancara singkat dengan guru serta siswa. Proses pembelajaran dilakukan secara tatap muka dengan memanfaatkan sumber belajar sederhana, seperti penjelasan langsung dari guru, diskusi kelompok, dan penggunaan bahan ajar ringkas. Hasil penelitian menunjukkan bahwa pembatasan penggunaan gawai tidak menghambat proses pembelajaran apabila guru mampu menerapkan strategi yang sesuai dengan kondisi siswa. Walaupun keterbatasan buku paket masih dirasakan, siswa menunjukkan peningkatan fokus, keaktifan, serta interaksi sosial yang lebih baik. Temuan ini menegaskan bahwa proses pendidikan tetap dapat berlangsung secara efektif meskipun berada dalam keterbatasan sarana pembelajaran.